Assessing continuum of trauma care for road accident victim in Jodhpur, Rajasthan. (30th September 2020) - Rustagi, N; Raghav, P; Dutt, N; Sinha, A; Rodha, M S
Abstract: Background: Road traffic injuries (RTIs) are a major public health problem, requiring concerted efforts both for their prevention and a reduction of their consequences. The present study was designed to assess the existing process of pre-hospital trauma care administered to road accident victims in a fast urbanizing city of Jodhpur, Rajasthan Methods: A cross-sectional study was designed from 1st November 2018 to 30th June 2019. All cases who were admitted to tertiary level trauma care facility in the study period were reviewed and were analyzed for type of injuries suffered, prehospital care services availed and the time duration that elapsed before patient arrived at tertiary health facility. Geographic information system was used to identify clustering of accident hot spots in the Jodhpur district. Results: A total of 137 patients or their caregivers were interviewed during the study period. A large proportion of patients 57(41.6%) were unconscious in post-crash phase. Private taxis contributed to maximum patient transfer (75.9%) and only 12.4% were transported through ambulance. Almost three fourth (78.1%) of patients received some form of pre-hospital care within 30 minutes of accident. About one third patients (35.7%) reached the trauma facility directly after the accident while majority (64.9%) were referred from other health facilities Conclusions: Pre-hospital trauma care for road traffic accident victims is available in golden hour for majority of victims in Jodhpur district. Victims from rural area and tourists form a sizeable proportion of accident victims brought to trauma care facility. The primary health care facilities play a pivotal role in managing victims as first point of care. Future research is thus warranted to explicitly examine the role of health professionals at primary health care facilities in administering pre-hospital trauma care. Key messages: The primary health care facilities play a pivotal role in managing victims as first point of care. In areas with evolving trauma systems, pre-hospital trauma care strengthening requires capacity building of all level of health professionals.